Clinical assessment of pontic design in anterior and posterior fixed partial denture patients: A crosssectional study - Mohammed Ibrahim Mathar (Bioinformation, 2026)
While several pontic designs are available in fixed prosthodontics, limited comparative clinical evidence exists regarding surface form, material selection and ridge deformities in anterior and posterior regions. A cross-sectional clinical study was conducted over 18 months on 80 adult patients rehabilitated with short-span (3-unit) FPDs, who were included and divided equally into anterior and posterior groups. A statistically significant association was observed between pontic design and esthetic appearance in the anterior region (p=0.011), with ovate pontics showing superior esthetic outcomes. In the posterior region, pontic design showed a highly significant association with cleansability (p < 0.001), with conical pontics exhibiting the most favourable hygiene scores. Thus, pontic design significantly influences esthetics in anterior FPDs and cleansability in posterior FPDs.